Pengaruh Likuiditas, Leverage, dan Return On Asset (ROA) terhadap Agresivitas Pajak pada Perusahaan Pertambangan yang Terdaftar pada Bursa Efek Indonesia - Ni Luh Wayan Intan Pratiwi, Ni Luh Wayan Intan Pratiwi; I Putu Julianto, S.E., M.Si., Ak (Universitas Pendidikan Ganesha, 2023)
The purpose of this study was to determine the effect of the variable liquidity, leverage and return on assets on tax aggressiveness either partially or simultaneously. This research is quantitative research conducted on mining sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The research sample was selected using purposive sampling with several criteria. There were 24 companies that were used as samples so that the number of research samples was 96 companies. However, there were 25 data that were outliers so that the final sample in this study was 71 samples. The data used in this study is secondary data obtained through the company's financial statements. The data analysis technique used consisted of a descriptive statistical test, a classical assumption test and a hypothesis test. The results obtained are liquidity and return on assets have a significant positive effect on tax aggressiveness while liquidity has no effect on tax liquidity. Simultaneously liquidity, leverage and return on assets have a significant effect on tax aggressiveness with an influence level of 26%.